Increased circulating levels of tissue kallikrein in systemic sclerosis correlate with microvascular involvement. Issue 3 (11th February 2005) - Del Rosso, A; Distler, O; Milia, A F; Emanueli, C; Ibba-Manneschi, L; Guiducci, S; Conforti, M L; Generini, S; Pignone, A; Gay, S; Madeddu, P; Matucci-Cerinic, M
Abstract : Background: In systemic sclerosis (SSc) the lack of an angiogenic response to hypoxia may be due to inappropriate synthesis of angiogenic and angiostatic factors. Tissue kallikrein (t-kallikrein), regulating the kallikrein-kinin system and acting on the microcirculation, is a potent angiogenic agent, and kallistatin is its natural inhibitor. Objective: To evaluate, in patients with SSc, t-kallikrein and kallistatin levels and their correlation with clinical features and measures of microvascular involvement. Patients and methods: Serum levels of t-kallikrein and kallistatin (ELISA) and t-kallikrein skin expression (immunohistochemistry) were studied in patients with SSc, and evaluated for subset (dSSc or lSSc), clinical and immunological features, and microvascular involvement (ulcers, telangiectasias, nailfold videocapillaroscopy). Results: Circulating levels of t-kallikrein were higher in SSc than in controls (p<0.001). T-kallikrein did not differ between lSSc and dSSc, although it was higher in lSSc than in controls (p<0.001).T-kallikrein levels were higher in patients with early and active capillaroscopic pattern than in those with late pattern (p = 0.019 and 0.023). Patients with giant capillaries and capillary microhaemorrhages had higher t-kallikrein concentrations than patients with architectural derangement (p = 0.04). No differences in kallistatin levels were detected between patients with SSc and controls, or between lSSc and dSSc. In early SSc skin, the presence of t-kallikrein was found in endothelial and in perivascular inflammatory cells, while no staining in skin of advanced SSc was detected. Conclusion: T-kallikrein levels are increased in patients with SSc, particularly in lSSc, and are associated with early and active capillaroscopic patterns. T-kallikrein may play a part in SSc microvascular changes.